ANALISIS HUBUNGAN MOTIVASI TERHADAP KINERJA PEGAWAI PADA PT. POS INDONESIA CABANG BANDAR LAMPUNG - Ferry Diawanto (Derivatif : Jurnal Manajemen, 2020)
This study is aims to examine the effects of motivation toward the employee performance at PT. Pos Indonesia, branch of Bandar Lampung. The results of calculations between variables X to Y using the Product Moment statistical test obtained r count of 0.488 which then the r count value was consulted with the Product Moment table at N = 42 then obtained information that the r table 0.304 for a 5% significant level while for a significant level of 1% is 0.393 so r count is greater than r table compared to the significant limit.If the r count of 0.488 is interpreted in the correlation coefficient with the interpretation index is at a value or number 0.400 - 0.599 which states that the value indicates a moderate correlation. So, the level of relationship between variables X and Y, namely Motivation to Increase Employee Performance including medium category intervals.The influence of motivation on employee performance improvement only reached 24%, while the effect of 76% came from other factors. The small degree of influence of X on Y due to Motivation (X) is only one factor that can affect the Improvement of Employee Performance.Based on this analysis, it is recommended that PT. Pos Indonesia Bandar Lampung branch still maintain and increase good work motivation so that employee performance can improve. In order for the work done by employees to produce optimal performance, then the work must provide inner satisfaction for workers or intrinsically motivate employees. And this intrinsic motivation must be designed in a work environment as a corporate culture program. Although employees still need external motivation such as salary to meet the satisfaction of their needs.Keywords: Motivation, Employee Performance